2016
DOI: 10.2147/ccid.s98633
|View full text |Cite
|
Sign up to set email alerts
|

Results from in vitro and ex vivo skin aging models assessing the antiglycation and anti-elastase MMP-12 potential of glycylglycine oleamide

Abstract: BackgroundGlycation is an aging reaction of naturally occurring sugars with dermal proteins. Type I collagen and elastin are most affected by glycation during intrinsic chronological aging.AimTo study the in vitro and ex vivo assays in human skin cells and explants and the antiaging effects of glycylglycine oleamide (GGO).Materials and methodsThe antiglycation effect of GGO was assessed in a noncellular in vitro study on collagen and, ex vivo, by immunohistochemical staining on human skin explants (elastin net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In a model of skin aging using UV irradiation on human skin explants, an antiaging cosmetic cream containing 0.05% RAL associated with Pre‐tocopheryl ® significantly reduced the UV‐generated free radicals, repaired laminin, elastic fiber and collagen network and stimulated collagen synthesis compared with a cream containing RAL alone . Another experimental study investigating the association of RAL, Pre‐tocopheryl ® and GGO (Relastide ® ) on fibroblasts and skin explants showed that these molecules exhibit antiaging properties by reversing the effects of oxidative damage, increasing proteasomal activity, stimulating the production of type I collagen, and decreasing metalloproteinase‐12 synthesis associated with skin aging . Those ex‐vivo studies support our observations that topical RAL in combination with Pre‐tocopheryl ® and GGO (Relastide ® ) is effective in improving skin appearance by acting on various cellular mechanisms involved in skin aging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a model of skin aging using UV irradiation on human skin explants, an antiaging cosmetic cream containing 0.05% RAL associated with Pre‐tocopheryl ® significantly reduced the UV‐generated free radicals, repaired laminin, elastic fiber and collagen network and stimulated collagen synthesis compared with a cream containing RAL alone . Another experimental study investigating the association of RAL, Pre‐tocopheryl ® and GGO (Relastide ® ) on fibroblasts and skin explants showed that these molecules exhibit antiaging properties by reversing the effects of oxidative damage, increasing proteasomal activity, stimulating the production of type I collagen, and decreasing metalloproteinase‐12 synthesis associated with skin aging . Those ex‐vivo studies support our observations that topical RAL in combination with Pre‐tocopheryl ® and GGO (Relastide ® ) is effective in improving skin appearance by acting on various cellular mechanisms involved in skin aging.…”
Section: Discussionsupporting
confidence: 93%
“…Glycylglycine Oleamide (GGO, Relastide ® ) is a lipopeptide with antioxidant and antiglycation properties. It was found to have a synergistic effect in association with RAL and protects skin elasticity . Pre‐tocopheryl ® , a vitamin E precursor, is a photostable antioxidant which was shown to increase collagen synthesis in vitro when associated with RAL .…”
Section: Introductionmentioning
confidence: 99%
“…Our ex vivo skin model confirmed that UVA induces alteration of the skin structure demonstrated by Boisnic et al 26 When adding, during the 48 hours following UVA irradiation, the tested combination, a restoration and improvement of the expression level of genes coding for the formation of elastin fibers, the cell–ECM interaction and the cytoskeleton, such as LOXL2 , FBLN1 , FBLN5 , FBN2 , ITGB1 , PXN and ACTA2 were observed paralleling findings made earlier when RAL, GGO and delta-TC were tested individually or after application of a combination of RAL and delta-TC in ex vivo skin samples. 18 , 24 , 26 , 27 The presently tested combination of 3 actives thus effectively protected skin tissues from UVA radiation and preserved the structure of both elastin and fibrillin-rich fibers preventing UVA-induced photoaging and preserving the elastic system organization. It is of note that a placebo preformulation was not efficient to protect the dermis against UVA, confirming the topical efficacy of the combined active ingredients.…”
Section: Discussionmentioning
confidence: 95%
“…Both are considered potential targets of antiaging products as demonstrated recently through in vitro and ex vivo studies on GGO. 24 …”
Section: Introductionmentioning
confidence: 99%
“…Several published studies or in vitro studies have linked carnosine with a protection against glycation when taken orally [6,7]. To our knowledge the antiglycation efficacy of topical carnosine in skin has not been published.…”
Section: Introductionmentioning
confidence: 99%